Path planning for mobile objects based on modification of the probabilistic roadmap method - Tran, Van Truc (Вестник Томского государственного университета. Управление, вычислительная техника и информатика)
The article formalizes the task of planning the trajectory of movement of mobile objects, and the mini-mum length of the trajectory is chosen as a criterion for the optimality of movement. When solving the problem, preference is given to the method of probabilistic route networks and modifications of this method are proposed. The study of the effectiveness of modified algorithms of probabilistic route networks is carried out using examples of solving the problem of automation and optimization of planning the trajectory of a mobile object in an external envi-ronment with restrictions on the size of the object. The developed software of the modified algorithms is illustrated by program listings and trajectories of movement of mobile objects.